The influence of educational transitions on loneliness and mental health from emerging adults’ perspectives - Amanda Jasmin Emilia Sundqvist; Pia Nyman-Kurkiala; Ottar Ness; Jessica Hemberg (International Journal of Qualitative Studies on Health & Well-Being)
Educational transitions can influence loneliness and increase mental health issues for young people transitioning between educational stages. The aim was to explore the link between educational transitions and emerging adults’ loneliness and mental health and how they perceive they can alleviate and/or improve these issues. Semi-structured qualitative interviews with a total of 12 emerging adults, 10 females and two males aged 18–29 (mean age, 22.91) were conducted. Data were analysed using qualitative content analysis. Emerging adults’ loneliness and mental health across educational transitions could be influenced by changes to their sense of security, for example concurrent transitions, increased academic demands, changed social network, insufficient attachment, lack of community, or changed physical environment. Transitions can be associated with positive expectations and self-development but also worry, emotional turmoil, loneliness, and mental health issues. A better transition experience can be enabled by increasing resources and activities and promoting a secure environment.